2019
DOI: 10.1186/s12880-019-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

Ratio and difference of the cross-sectional area of median nerve to ulnar nerve in diagnosing carpal tunnel syndrome: a case control study

Abstract: Background To evaluate the diagnostic accuracy of the median-to-ulnar nerve ratio (MUR) and the median-to-ulnar nerve difference (MUD) in patients with carpal tunnel syndrome (CTS). Methods In this study, 32 patients with CTS and 32 healthy volunteers were evaluated. All participants received a series of tests and ultrasound examination for the evaluation of the following criteria: cross-sectional area of the median nerve at the pisiform level (CSA-P), swelling ratio (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The diagnostic value of wrist median nerve CSA vs. wrist-to-forearm ratio showed inconsistent results in literature ( 30 , 31 ). A cross-sectional study published in 2019 by Chang et al suggests the ulnar nerve compared to the median nerve at wrist level could serve as internal control by using median-to-ulnar-nerve difference instead of the median-to-ulnar-nerve ratio ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of wrist median nerve CSA vs. wrist-to-forearm ratio showed inconsistent results in literature ( 30 , 31 ). A cross-sectional study published in 2019 by Chang et al suggests the ulnar nerve compared to the median nerve at wrist level could serve as internal control by using median-to-ulnar-nerve difference instead of the median-to-ulnar-nerve ratio ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, ultrasonography is used to diagnose CTS according to the following criteria: (1) increased CSA of the median nerve, (2) increased flattening ratio (FR; the ratio of the length of the long axis to that of the short axis of the median nerve), and (3) increased palmar bowing of the flexor retinaculum [ 6 , 7 ]. Moreover, the swelling ratio (the ratio of the CSA of the median nerve at carpal tunnel to that at the forearm level), and ratio and difference in CSA between the median and ulnar nerves have also been used to accommodate intersubject variations [ 8 , 9 ]. Some studies also observed increased intraneural blood flow in the median nerve on patients’ color or power Doppler ultrasonograms [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, using a single cutoff value for the CSA of the median nerve has been argued to underestimate the prevalence rate of CTS, given the variations in body weight, age, and sex among individuals [ 4 , 5 ]. Therefore, alternative methods have been proposed for ultrasound examination of CTS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative methods have been proposed for ultrasound examination of CTS patients. For example, comparative methods such as the swelling ratio and ulnar to median ratio use the median nerve at the forearm level or ulnar nerve at the wrist level as an internal control to improve the diagnostic accuracy [ 4 , 6 9 ]. Using power Doppler ultrasonography to evaluate the intraneural vascularity of the median nerve, on the other hand, has also emerged in recent years as another method to assist in diagnosing CTS [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%